Emotional temperament in food-related metaphors: a cross-cultural account of the conceptualisations of ANGER - Zahra Khajeh,; Imran Ho Abdullah,; Kim, Hua Tan (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2014)
The manner temperaments manifested with the semantic domain of eating and food in a certain culture can be understood through a discussion of dietetic and culinary concepts of a particular culture. What people in a society and culture eat or like to eat may become an evaluation of their emotional temperaments and therefore an implication for portrayal of their specific cultural models. Calling into question the strong claims of ‘embodiment’ as an underlying motivation for emerging specific metaphorical concepts by Conceptual Metaphor Theory (Lakoff and Johnson 1980, 1999; Lakoff and Kövecses 1987), the close investigation of metaphorical uses of food-related concepts in Persian manifests that, in spite of some correspondences to those in English, ANGER metaphorical concepts are distinctive. The conceptual metaphor disparities highlight many vestiges of Galenic Theory, and Iranian Traditional Medicine Theory, suggesting that the cultural model of humoralism and dietetics have mingled in Persians’ life style. This is because their effects have been extended into Persian metaphoric language, and cognitive conceptualisations of ANGER emotion.